PENGARUH PELATIHAN EVAKUASI BANJIR TERHADAP PENGETAHUAN DAN SIKAP APARAT KEPOLISIAN DI KOTA MAKASSAR - Harini, Atik; Dirawan, Gufran D. (UNM Environmental Journals, 2023)
All over the world floods are recognized as one of the most detrimental natural disasters. This study aims to determine the amount of knowledge of the police regarding flood evacuation and the attitude of the police apparatus in carrying out flood evacuation. the research method used descriptive quantitative with sampling using purposive sampling so that a sample of 20 police officers was obtained. Furthermore, the analysis technique was carried out by paired sample t test to see the difference before and after being given training on flood evacuation. The results showed that there was an increase in the knowledge and attitude of the police after being given flood evacuation training.